6.6k views
4 votes
Solve the equation below.
6(-2w - 3) = -4(3w + 7) + 10

1 Answer

7 votes

Answer: all real numbers

Step-by-step explanation:

Let's solve your equation step-by-step.

6(−2w−3)=−4(3w+7)+10

Step 1: Simplify both sides of the equation.

6(−2w−3)=−4(3w+7)+10

(6)(−2w)+(6)(−3)=(−4)(3w)+(−4)(7)+10(Distribute)

−12w+−18=−12w+−28+10

−12w−18=(−12w)+(−28+10)(Combine Like Terms)

−12w−18=−12w+−18

−12w−18=−12w−18

Step 2: Add 12w to both sides.

−12w−18+12w=−12w−18+12w

−18=−18

Step 3: Add 18 to both sides.

−18+18=−18+18

0=0

User Lauda  Wang
by
5.5k points